The Common Currency of Psychological Distance. (August 2013) - Maglio, Sam J.; Trope, Yaacov; Liberman, Nira
People's thoughts often go beyond what is right in front of them. In so doing, they mentally traverse psychological distance: They think about the past or the future, other places, other people, and wonder about the impossible. These four dimensions all tap into the same common construct of distancing from immediate experience. As a result, people associate each type of distance with the others and infer that anything far in one way will be far in all the other ways. Furthermore, distance causes further distance to shrink in the mind's eye, even if in a different form than the first. We consider potential differences whereby certain distances might be understood in terms of other distances, and then we evaluate additional contenders that might qualify as distinct dimensions of distance in their own right. Throughout, we highlight implications of these principles for everyday judgment and decision making.